Peran Satuan Binmas dalam Melakukan Penyuluhan Guna Mencegah Penyalahgunaan Narkoba di Wilayah Hukum Polres Majalengka - Zuldi Nayaka (Police Studies Review, 2020)
The background that underlies this research is an increase in the number of drug abuse in Indonesia, especially in the Majalengka area, which has increased in the last 4 years. Therefore, a study was carried out aimed at finding a general picture of the Majalengka area, binmas unit of Majalengka Regional Police and drug abuse that occurred in Majalengka. In addition, it is also to find out the factors that influence and the steps taken in conducting counseling to prevent drug abuse. This research uses a qualitative approach and uses data collection techniques through observation, interviews and document studies. The results showed that the role of counseling by the Binmas Unit in preventing drug abuse in the Majalengka District Police jurisdiction was still not optimal. Although there is cross-functional cooperation to conduct counseling so that the material conveyed by the community can be well absorbed, there are still obstacles in the organization in the form of a lack of quantity and quality of members, so it impedes organizing activities. Then the counseling that was done was also still not in accordance with the applicable rules, which in the article were done with eight methods, only done with three methods. Overall managerial activities are still hampered, the counseling activities carried out by the Binmas Unit have not been maximized. Guided by the results of research conducted, the authors suggest to support the success in counseling activities in preventing drug abuse in the jurisdiction of Majalengka Regional Police in the need for more education for Binmas Unit personnel about. Then the leadership's attention is needed on the quantity of personnel in the Majalengka Police Binmas Unit because it does not meet the DSP. In addition, the authors also suggest conducting training to members of the Binmas unit about the material to be conveyed to the public in the form of general knowledge about drugs, the dangers of drugs as well as the law that ensnare them.